PEMELIHARAAN HAZARD DI PADANG GOLF MATOA NASIONAL, JAKARTA SELATAN - Samsud Dlukha; Sitti Wardiningsih; Yusi Febriani; Ray March Syahadat; Priambudi Trie Putra (BUANA SAINS, 2017)
Padang Golf Matoa Nasional is a 18 hole golf course that located in South Jakarta and designed with international standards. A game area of golf courses consist of several zones. The zones need to be maintained by form of ideal and maintenance activities. This study focuses on the maintenance of hazard zones (bunkers, water hazards, and rough) as important part of the golf game area. The purpose of this article provides recommendations on system maintenance hazard in Padang Golf Matoa Nasional so that the quality of the landscape and the game remains optimal. The results obtained in general maintenance hazard zone has been good. To realize optimal results, it is required labor ratios ranging from 1:0,1 to 1:0,3. Furthermore, it is needed to increase the number and renewing putty knife and hoe for effective use of maintenance process.